2018
DOI: 10.1212/nxi.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Glycine receptor modulating antibody predicting treatable stiff-person spectrum disorders

Abstract: BackgroundGlycine receptor alpha-1 subunit (GlyRα1)-immunoglobulin G (IgG) is diagnostic of stiff-person syndrome (SPS) spectrum but has been reported detectable in other neurologic diseases for which significance is less certain.MethodsTo assess GlyRα1-IgGs as biomarkers of SPS spectrum among patients and controls, specimens were tested using cell-based assays (binding [4°C] and modulating [antigen endocytosing, 37°C]). Medical records of seropositive patients were reviewed.ResultsGlyRα1-IgG (binding antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 17 publications
2
68
0
Order By: Relevance
“…The different antibodies have different management implications as they stand for different underlying pathophysiological mechanisms that reflect on links with autoimmune or paraneoplastic disease, and treatment responses (Table ) …”
Section: Diagnostic Work‐up: Clinical Spectrum Implications Of Antibmentioning
confidence: 99%
“…The different antibodies have different management implications as they stand for different underlying pathophysiological mechanisms that reflect on links with autoimmune or paraneoplastic disease, and treatment responses (Table ) …”
Section: Diagnostic Work‐up: Clinical Spectrum Implications Of Antibmentioning
confidence: 99%
“…47 Hinson et al examined the prevalence of IgG reactive to the α-1 subunit of the glycine receptor in sera and CSF from a group of 247 patients within the spectrum of stiff person syndrome (SPS), including classical SPS, progressive encephalomyelitis with rigidity and myoclonus (PERM), stiff limb or stiff trunk syndrome, and isolated exaggerated startle (hyperekplexia). 48 SPS is classically associated with 65-kd isoform of glutamic acid decarboxylase (GAD65) antibodies, but this study explored the emerging association with glycine receptor antibodies. Seropositivity against the GlyRa1 subunit was detected in 19 of 20 patients, and in CSF in 4 of 10 patients, one of who did not have detectable antibody in serum, for an overall rate of 8.5%.…”
Section: Antibodies Directed Against Intraneuronal Antigensmentioning
confidence: 99%
“…Seropositivity against the GlyRa1 subunit was detected in 19 of 20 patients, and in CSF in 4 of 10 patients, one of who did not have detectable antibody in serum, for an overall rate of 8.5%. 48 Reminiscent of acetylcholine receptor pathophysiology in myasthenia, the authors also described development of a modulating (in addition to validation of the cell-based binding) assay, 48 and suggested that application of such second-generation or reflexive testing strategies could increase diagnostic specificity. It is important to note, however, that this test was developed and analyzed via expression of a recombinant antigen in a widely available established nonneural (HEK 293) cell line, and the effect of receptor internalization as it relates to relevant extracellular protein remains to be determined in actual neural populations in situ.…”
Section: Antibodies Directed Against Intraneuronal Antigensmentioning
confidence: 99%
“…SPS patients show a similar phenotype compared to patients suffering from startle disease including stiffness and painful spasms especially in axial and proximal limb muscles ( Bhatti and Gazali, 2015 ; Dalmau et al, 2017 ). The most efficient treatment is immunotherapy but patient relapses are common ( Hinson et al, 2018 ), which demonstrates that SPS is treatable but remediless. In contrast to mutations in GlyR genes underlying startle disease, SPS patients carry GlyR autoantibodies.…”
Section: Introductionmentioning
confidence: 99%